Ilmu Sosial Profetik: Etika Pengembangan Ilmu-Ilmu Sosial - K Kuntowijoyo (Al-Jami'ah: Journal of Islamic Studies, 1998)
For muslim, the 19th century is very important. It was seen as the era of deep influence of western ideas on muslim society and also believed to have created the so-called modern society, in which positivistic approach in the social sciences become very dominant. This has, as many people say, more or less brought the promotion of, usually called, value-free approach in social science and, consequently, religious outlook is considered distinct and must be detached from scientific consideration. In the late 20th century, however, criticsm toward modern social science has often been raised which, in turn, encourages the emergence of the so-named post-modernism. This, in fact, promotes, among other things, the idea that value can not be separated from scientific activities. It is certainly in this context that this following article can properly be understood, in the sense that, according to the writer, values (e.g.Islamic values) should become an integral part of the scholars’ activities. For this purpose, this article introduces what it calls ilmu soasial profetik (aSocial Prophetic Science), a science consisting of the following three important elements. Amar ma’ruf (emancipation), nahi munkar (liberation), and tu’minūna billah (transcendence). These all are based on the sunnah of the prophet Muhammad SAW, the ideal type for Muslim, or even for all human being. In this effort, the writer tries to combine certain religious terms common to the traditional Muslim with those known in the scientific approach. In the end, this paper convincingly states that Ilmu Sosial Profetik will surely be able to create an ideal ummah who are able to think scientifically without loosing their religious belief.